225k views
0 votes
X dx − y^2 dy = 0, y(0) = 1

User Malak
by
4.1k points

1 Answer

4 votes

Answer:


y=\sqrt[3]{3x^2+1}

Explanation:

Given differential equation,


xdx-y^2dy=0


\implies y^2dy=xdx

Integrating both sides,


\int y^2 dy=\int xdx


(y^3)/(3)=x^2+C

We have, y(0) = 1,

That is, y = 1 when x = 0,


\implies (1)/(3)=0+C\implies C = (1)/(3)


\implies (y^3)/(3)=x^2+(1)/(3)


y^3=3x^2+1


\implies y=\sqrt[3]{3x^2+1}

User Enrico Carlesso
by
6.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.